PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA AGEN ASURANSI (STUDI KASUS PADA SELURUH AGEN ASURANSI AJB BUMIPUTERA CABANG PANDANARAN) - Desbrian Vidi Pradana; Hari Susanta Nugraha; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the increasingly strict business world, accompanied by the times that requires every company to be able to improve the performance of each employee. One of the services that can be affected by the times are insurance. Insurance services become important to see how health condition can be uncertain for every people so that they need a protection called insurance. However, in the period 2011-2014 year results that insurance agent performance of AJB Bumiputera branch Pandanaran fluctuated. If this is not addressed then feared insurance agent of AJB Bumiputera branch Pandanaran can not meet the targets from company and making them increasingly lagging from other insurance company. The purpose of this study was to determine the effect of competency and compensation on insurance agent performance of AJB Bumiputera branch Pandanaran. This research method is explanatory, with data collection through questionnaires and interviews. The sampling technique used saturated technique sampling. The respondents are 57 peoples whom are insurance agent of AJB Bumiputera branch Pandanaran. The analysis technique used was quantitative. Quantitative analysis using validity, reliability, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test). The results of this study showed a relatively good level of competency. Compensation is in high category, although there are still existing in the low category. Good insurance agent performance, but still there are insurance agent who have bad performance. All independent variables, namely competency (X1) and compensation (X2) together (simultaneously) or individually (partial) affect insurance agent performance dependent variable (Y). Advice can be given that adding some facilities that can make insurance agent work easier. In addition, companies need to provide advanced training for insurance agent and guidance from their supervisor, considering the standard of the company that changes according to market conditions at that time. And the need for continued research by the company or outside the company regarding other variables that can provide additional contributions to improve insurance agent performance.